Evaluation of the effects of health impact assessment practice at the local level in Monteregie. Issue 1 (December 2016) - Nour, Kareen; Dutilly-Simard, Sarah; Brousselle, Astrid; Smits, Pernelle; Buregeya, Jean-Marie; Loslier, Julie; Denis, Jean-Louis
Abstract Background In Quebec (Canada), the Monteregie Regional Public Health Department has chosen to use health impact assessment (HIA) to support municipalities through a knowledge exchange and collaborative process in order to positively influence decision-making regarding local policies and projects. The value of HIA is becoming increasingly recognized by municipalities interested in planning and managing their cities with an eco-systemic perspective. However, the knowledge and tools which support the use of the HIA at regional and local levels are still missing. Methods The general objective is to evaluate the impact the collaborative HIA process used in Monteregie has had on the formulation, adoption and implementation of policies and projects favourable to health. The methodology is based on Mayne's CA design, which allows the identification of factors which contribute to a change process. It is described as one of the best approaches to reduce uncertainty regarding the observed results and the contribution of a program. All of the HIA processes realised between January 2013 and January 2016 in Monteregie will be studied following a case study strategy. Study populations include regional and local public health professionals, municipal officers and community members implicated in these HIAs. Various qualitative and quantitative methods will be used, including examination of documentation, observations on the city grounds, and individual or group interviews. A model of change will be constructed for each HIA process and will present the logical pathway which leads to the observed results, alternative explanations and hypothesises as to why these results were obtained, and contextual factors that could have influenced them. This model will allow the production of a refined contribution story for each HIA. A convergence and divergence analysis will be completed in order to identify differences or similitudes between the different HIAs studied. Discussion In addition to contributing to the production of knowledge in relation to the collaborative model of HIA, this research project will allow other regional and local public health actors and municipalities of Quebec or other decision-making and political bodies to understand the usefulness of this approach for the improvement of population health and well-being.